Moral Value and Character Building Education in Folklore from Central Java “Timun Mas” - Dilla Dwi Nanda; Betty Simbolon; Friska Afriana Damanik; Yenita Br Sembiring (Journal of Languages and Language Teaching, 2021)
Folklore is a story that originated in society and developed in society in the past which played an important role in the development of children's character learning in the form of moral values. The purpose of this study was to explain the moral values contained in folklore to improve character education. This study used a qualitative descriptive research design. Where all the data collected is based on books and other supporting document data. From the discussion of the Timun Mas folklore, there are eight prominent moral values, namely religious values, independent values, curiosity values, hard work values, responsibility values, honesty values, creativity, the value of the spirit of hard work. And from the research results, it can be concluded that the folklore of Timun Mas has many moral values that can be applied in the world of Education to shape character.